An analysis of the heterogeneity and IP packet reordering over multiple wireless networks - Kaspar, D.; Evensen, K.; Hansen, A.F.; Engelstad, P.; Halvorsen, P.; Griwodz, C. (2009 IEEE Symposium on Computers and Communications, 2009)
With the increasing deployment of wireless technologies, such as WLAN, HSDPA, and WiMAX, it is often the case that simultaneous coverage of several access networks is available to a single user device. In addition, devices are also often equipped with multiple network interfaces. Thus, if we can exploit all available network interfaces at the same time, we can obtain advantages like the aggregation of bandwidth and increased fault tolerance. However, the heterogeneity and dynamics of the links also introduce challenges. Due to different link delays, sending packets of the same flow over multiple heterogeneous paths causes the reordering of packets. In this paper, we quantify the impact of network heterogeneity and the use of multiple links on IP packet reordering. We show with practical measurements, according to commonly used metrics, that packet reordering over multiple links exceeds the reordering caused by common connections in high-speed, wide- area networks. We also demonstrate that heterogeneity and reordering exceed the assumptions presented in related work. By using sufficiently large buffers, packet reordering can be avoided. However, for devices with high resource constraints, the workload of using large buffers is expensive. Sender-side solutions of dividing and scheduling a packet sequence over multiple links can reduce the buffer requirements at the receiver. Initial experiments with a static scheduler, that has knowledge of average link delay and throughput estimates, show that packet reordering can be reduced by only 38% due to the dynamic heterogeneity of the two links.